Exploring Customer-Object Assemblages in Digital Content Consumption: - Masao Kakihara (Maketingu Janaru)
This study examines the bidirectional and co-creative consumer experience between VTubers and their audiences based on Hoffman and Novak’s (2018) “Consumer–Object Assemblages” theory. VTubers represent a novel form of creators who perform online through digital avatars. Through both quantitative surveys and qualitative interviews, the study revealed that VTuber audiences engage in various forms of interaction that evoke “enabling” and “constraining” experiences, as proposed by Hoffman and Novak. These bidirectional, co-creative experiential processes manifest differently across distinct fan segments. The findings underscore the effectiveness of this theoretical framework for understanding consumer behavior in digital environments, particularly in contexts where products and services, such as smart devices and AI agents, exhibit autonomous behavior.